The Taming of the Shrewd: A Reappraisal of the Interests of the Company as a Control on Directorial Autonomy - Gavin, Philip (Trinity College Dublin. School of Law. Discipline of Law, 2023)
This thesis examines how differing conceptions of the company's interests can affect the autonomy of directors. This involves a comparative analysis across five common law jurisdictions: Ireland, the United Kingdom, Delaware, Canada and Australia, looking at how each jurisdiction judicially or legislatively frames the duty of directors to act in good faith in what they consider to be in the interests of the company. This firstly examines theoretical accounts of what falls within the company's interests spanning various economic and sociological accounts of the company alongside shareholderist and stakeholderist conceptions of corporate purpose. Building upon this theoretical framework later chapters explore the doctrinal understanding of the company's interests at common law and their reappraisal in legislative reform. The contextual nature of the company's interests is also examined, with how differently or narrowly the company's interests are framed in circumstances such as takeovers or insolvency. These differing conceptions of the company's interests are not primarily approached for their normative value. The central research question is instead to what extent the scope of directorial autonomy is contingent upon how the interests of the company are understood. This thesis therefore explores how reappraisals of the company's interests will position directors in their capacity to exercise autonomy over their business judgment and approach towards the company's interests. The position of directors is approached as a trade-off between authority and accountability and whether reappraisals to the company's interests are to be seen as stymying or bolstering directorial autonomy. The means by which the company's interests can act as an accountability mechanism are explored through legal accountability and judicial deference to good faith business judgment. Market accountability is also explored namely through reporting requirements, stakeholder monitoring and residual control. Doctrinal reappraisals of the company's interests may merely recognise the commercial status-quo that the company's interests are inherently multi-faceted. Complexified accounts of the company's interests may accordingly do more to reinforce deference to business judgment than achieve new avenues of accountability. This thesis concludes that any ongoing reappraisal of the company's societal role and broadened interests are to be approached principally for their impact on directorial autonomy and business judgment.
APPROVED
Keywords: Directors' Duties; Corporate Governance; The Interests of the Company; Business Judgment; Good Faith; Directors; Shareholders; Stakeholders; Creditors; Takeovers; Insolvency